Pengaruh Motivasi, Lingkungan Kerja Dan Pelayanan Terhadap Kinerja Pegawai - Zalmah; Darmawan, Cecep; Widjaja, Yani Restiani; Riswanda, Jhon (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Human resources are key to organizational success. A decline in employee performance can result from poor working conditions and excessive workloads. Improvement requires a focus on a supportive work environment and balanced workloads for optimal performance. This study employed multiple linear regression on 52 employees to analyze the relationship between work environment (X1), workload (X2), and employee performance (Y). The results showed a significant influence of the work environment and workload, but these factors only accounted for 33.9% of the total impact on performance, indicating that 66.1% is attributed to other factors. Further studies are needed to understand behavioral changes affecting performance. Companies should prioritize a comfortable work environment, address employee needs, and ensure proper task allocation to achieve service targets.